Rewrite the equation as <math><mstyle displaystyle="true"><mi>b</mi><mo>+</mo><mn>2</mn><mi>s</mi><mo>=</mo><mi>P</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mn>2</mn><mi>s</mi><mo>=</mo><mi>P</mi><mo>-</mo><mi>b</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>s</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Move the negative in front of the fraction.

Do you know how to Solve for s P=b+2s? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.